2021
DOI: 10.1186/s12917-021-02773-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the growth, ileal digestibility, intestinal histology, behavior, fatty acid composition of the breast muscles, and blood biochemical parameters of broiler chickens by dietary inclusion of safflower oil and vitamin C

Abstract: Background The effects of safflower oil and vitamin C (Vit. C) inclusion in broiler chicken diets on the growth performance, apparent ileal digestibility coefficient “AID%” of amino acids, intestinal histology, behavior, carcass traits, fatty acid composition of the breast muscle, antioxidant and immune status for a 35-day feeding period were evaluated. A total of 300 three-day-old Ross chicks (58.25 g ± 0.19) were randomly allotted in a 2 × 3 factorial design consisting of two levels of vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 86 publications
2
30
0
Order By: Relevance
“…For instance, Vit C can directly function as an antioxidant to protect against lipid peroxidation in immune-related cells [ 13 , 14 ], whereas other functional nutrients may have indirect actions on immune cell proliferation and activity by decreased corticosteroid production, increased immune organ development, and modulated nutrient metabolism [ 12 , 16 , 18 ]. Furthermore, it is also likely that the endogenous synthesis of Vit C in broiler chickens may be impaired or insufficient to satisfy increased requirement of Vit C to potentiate immune responses of broiler chickens exposed to heat stress; this may be the reason why dietary supplementation of 250 mg/kg Vit C exerted the positive effects on immune responses of broiler chickens [ 50 ]. However, it is still uncertain why other functional nutrients did not show such a positive effect as observed by dietary supplementation of Vit C. Therefore, more research is required to compare immune modulations by various functional nutrients in broiler diets under heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Vit C can directly function as an antioxidant to protect against lipid peroxidation in immune-related cells [ 13 , 14 ], whereas other functional nutrients may have indirect actions on immune cell proliferation and activity by decreased corticosteroid production, increased immune organ development, and modulated nutrient metabolism [ 12 , 16 , 18 ]. Furthermore, it is also likely that the endogenous synthesis of Vit C in broiler chickens may be impaired or insufficient to satisfy increased requirement of Vit C to potentiate immune responses of broiler chickens exposed to heat stress; this may be the reason why dietary supplementation of 250 mg/kg Vit C exerted the positive effects on immune responses of broiler chickens [ 50 ]. However, it is still uncertain why other functional nutrients did not show such a positive effect as observed by dietary supplementation of Vit C. Therefore, more research is required to compare immune modulations by various functional nutrients in broiler diets under heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary addition of various antioxidants such as vitamin C, vitamin E, and selenium was efficiently practiced, mitigating oxidative stress in vivo and in animal products [25][26][27][28][29]. Vitamin E is a coating antioxidant that protects the intracellular structures of live organisms.…”
Section: Introductionmentioning
confidence: 99%
“…It also works to replenish the reduced vitamin E. Vitamin C cannot directly eliminate the lipophilic radicals formed in the membranes, but it reduces the number of tocopheroxyl radicals that adhere to the membrane during the transition of the lipophilic to the aqueous phase [31]. Numerous investigations disclosed good performance with supplementing of vitamins (C and E) in broiler chick diets [12,26,27,32] or fish [25,28,33,34]. Recently, different reports have been reported that vitamins E and C, due to the fact of their role as antioxidants, can protect against toxic infections from xenobiotics and those from minerals, too [35].…”
Section: Introductionmentioning
confidence: 99%
“…The high dose group (400 μg/g) was 0.11 ± 0.03 mm, which was restored to the level of the normal group (Figure 4D). The depth of colonic crypt is the number of cells in the longitudinal half of each crypt, reflecting the balance between the proliferation and apoptosis of intestinal epithelial cells [32]. Studies have shown that a variety of carcinogens or bacteria can induce the change of crypt depth and destroy the balance.…”
Section: Effect Of Scs On the Colonic Crypt Depthmentioning
confidence: 99%